Barley Melanoidins: Key Dietary Compounds With Potential Health Benefits - Sharma, Jitendra Kumar; Sihmar, Monika; Santal, Anita Rani; Prager, Louis; Carbonero, Franck; Singh, Nater Pal (Frontiers in Nutrition, 2021)
This paper is a review of the potential health benefits of barley melanoidins. Food melanoidins are still rather understudied, despite their potential antioxidant, antimicrobial, and prebiotic properties. Free radicals are villainous substances in humans produced as metabolic byproducts and causing cancers and cardiovascular diseases, and the melanoidins alleviate the effects of these free radicals. Malt is produced from cereal grains such as barley, wheat, and maize, and barley is predominantly used in beer production. Beer (alcoholic and non-alcoholic) is a widely consumed beverage worldwide and a good source of dietary melanoidins, which enhance the beers' flavor, texture, and sensorial properties. Melanoidins, the final products of the Maillard reaction, are produced at different stages during the brewing process. Beer melanoidins protect the cells from oxidative damage of DNA. The high reducing capacity of melanoidins can induce hydroxyl radicals from H2O2 in the presence of ferric ion (Fe3+). Melanoidins inhibit lipid peroxidation during digestion due to their chelating metal property. However, lower digestibility of melanoidins leads to less availability to the organisms but is considered to function as dietary fiber that can be metabolized by the lower gut microbiota and possibly incur prebiotic properties. Melanoidins promote the growth of Lactobacilli and Biﬁdobacteria in the gastrointestinal tract, preventing the colonization of potential pathogens. Barley is already popular through beer production and increasingly as a functional food. Considering this economic and industrial importance, more research to explore the chemical properties of barley melanoidins and corresponding health benefits as barley is warranted.